Synthesis and Photocatalytic Properties of CuO-CuS Core-Shell Nanowires - Kao, Yuan-Tse (Materials (Basel), 2019)
In this study, an efficient method to synthesize CuO-CuS core-shell nanowires by two-step annealing process was reported. CuO nanowires were prepared on copper foil via thermal oxidation in a three-zone horizontal tube furnace. To obtain larger surface area for photocatalytic applications, we varied four processing parameters, finding that growth at 550 °C for 3 h with 16 °C/min of the ramping rate under air condition led to CuO nanowires of appropriate aspect ratio and number density. The second step, sulfurization process, was conducted to synthesize CuO-CuS core-shell nanowires by annealing with sulfur powder at 250 °C for 30 min under lower pressure. High-resolution transmission electron microscopy studies show that a 10 nm thick CuS shell formed and the growth mechanism of the nanowire heterostructure has been proposed. With BET, the surface area was measured to be 135.24 m(2)·g(−1). The photocatalytic properties were evaluated by the degradation of methylene blue (MB) under visible light irradiation. As we compared CuO-CuS core-shell nanowires with CuO nanowires, the 4-hour degradation rate was enhanced from 67% to 89%. This could be attributed to more effective separation of photoinduced electron and hole pairs in the CuO-CuS heterostructure. The results demonstrated CuO-CuS core-shell nanowires as a promising photocatalyst for dye degradation in polluted water.